Nota sobre la etiologia de la podredumbre del tallo del clavel en la Argentina - Wolkan, S.M.=700 1 Ronco, B.L.; Lori, G.A.
(Es, En)
ilus., 16 ref.
Keywords: PODREDUMBRES; TALLO; GIBBERELLA FUJIKUROI; FUSARIUM; ARGENTINA; PODREDUMBRE DEL TALLO; CLAVEL